Implementasi dan Efektivitas Pelaksanaan Undang-Undang Pengampunan Pajak Dan Program Pengungkapan Sukarela - Amin, Muhammad; Machmud, Aris (LPPM Universitas Ekasakti Padang, 2024)
The principle of taxation must fulfill the element of justice for all taxpayers including in the tax amnesty program. The elimination of taxes that should be owed and tax sanctions for taxpayers who participate in the tax amnesty program and the Voluntary Disclosure Program (PPS) is done by paying ransom. However, the small amount of ransom payment is allegedly not fulfilling the element of legal justice. The purpose of this study is to determine the implementation and effectiveness of the Tax Amnesty Law and PPS. The method used in this research is the normative juridical law study method, using a statutory approach in studying, examining and exploring the problems in this study. The conclusion is that the elimination of taxes that should be payable does not fulfill the principle of justice, while the exemption of tax sanctions has fulfilled the principle of justice. The implementation of the tax amnesty program is ineffective due to the insignificant tax revenue and compliance of tax return submission after tax amnesty and PPS, as well as the increase in tax ratio which tends to stagnate and even still below neighboring countries in ASEAN.